Performance Assessment of Concrete Structures and Engineered Barriers for Nuclear Applications Conclusions of RILEM TC 226-CNM - L'Hostis, Valérie; Gens, Robert (RILEM State-of-the-Art Reports, 2016)
The main outcomes of RILEM TC-226-CNM are summarized in this book. Key input was provided by researchers from countries that are main contributors in the R&D, design, construction, operation, and regulation of waste nuclear reinforced concrete facilities. Nuclear power plants and many of the facilities and structures used for the management of radioactive waste materials generated by the fuel cycle use concrete in their construction. RILEM TC 226 CNM covered several areas including functional and performance requirements for concrete structures; degradation processes; phenomenological modelling, field experiences, tests approaches, instrumentation and monitoring methods dedicated to performance assessments; service-life models; aging Management of Nuclear Power Plants, repair techniques; codes and standards specific to radioactive waste facilities.  .